Comparative Characterization of Vibrio cholerae O1 from Five Sub-Saharan African Countries Using Various Phenotypic and Genotypic Techniques - Smith, Anthony M. (PLoS One, 2015)
We used standardized methodologies to characterize Vibrio cholerae O1 isolates from Guinea, Democratic Republic of the Congo (DRC), Togo, Côte d’Ivoire and Mozambique. We investigated 257 human isolates collected in 2010 to 2013. DRC isolates serotyped O1 Inaba, while isolates from other countries serotyped O1 Ogawa. All isolates were biotype El Tor and positive for cholera toxin. All isolates showed multidrug resistance but lacked ciprofloxacin resistance. Antimicrobial susceptibility profiles of isolates varied between countries. In particular, the susceptibility profile of isolates from Mozambique (East-Africa) included resistance to ceftriaxone and was distinctly different to the susceptibility profiles of isolates from countries located in West- and Central-Africa. Molecular subtyping of isolates using pulsed-field gel electrophoresis (PFGE) analysis showed a complex relationship among isolates. Some PFGE patterns were unique to particular countries and clustered by country; while other PFGE patterns were shared by isolates from multiple countries, indicating that the same genetic lineage is present in multiple countries. Our data add to a better understanding of cholera epidemiology in Africa.